2020
DOI: 10.3390/cosmetics7020040
|View full text |Cite
|
Sign up to set email alerts
|

Broussonetia papyrifera Promotes Hair Growth Through the Regulation of β-Catenin and STAT6 Target Proteins: A Phototrichogram Analysis of Clinical Samples

Abstract: Broussonetia papyrifera (B.papyrifera), belonging to the Moraceae family, is known to elicit anti-inflammatory, antioxidant, anti-tyrosinase, anticancer, antinociceptive, and antimicrobial effects. The present study has been designed to examine the effects of B. papyrifera extract on hair growth through in vitro and clinical samples. Real-time cell growth assay, T-cell factor/lymphoid enhancer-binding factor (TCF/LEF), activation of signal transducer and activator of transcription-6(STAT6) and STAT3 reporter g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In 2020, CSZ extract increased liver function and alleviated DILI in rats induced in acetaminophen (APAP) via regulating the TLR3/JNK/c-jun/c-fos/JAK/STAT3 pathway [107]. In 2020, Lee et al [108] showed that ethanolic extract of BP had the capacity of promoting hair growth by regulating β-Catenin and STAT6 target proteins in human hair follicle dermal papilla (hHFDP) cells within a dose of 0-20 µg/mL. In 2014, the ethanolic extract of BK twigs was found to have anti-angiogenic activities with a dosage of 0.1-10 µg/mL; the mechanisms were the inhibition of VEGF-A, stimulated by the phosphorylation/activation of ERK, Akt, and p70S6K, and the downregulation of VEGFR-2 and MMP-2 in human umbilical vein endothelial cells [109].…”
Section: Other Propertiesmentioning
confidence: 99%
“…In 2020, CSZ extract increased liver function and alleviated DILI in rats induced in acetaminophen (APAP) via regulating the TLR3/JNK/c-jun/c-fos/JAK/STAT3 pathway [107]. In 2020, Lee et al [108] showed that ethanolic extract of BP had the capacity of promoting hair growth by regulating β-Catenin and STAT6 target proteins in human hair follicle dermal papilla (hHFDP) cells within a dose of 0-20 µg/mL. In 2014, the ethanolic extract of BK twigs was found to have anti-angiogenic activities with a dosage of 0.1-10 µg/mL; the mechanisms were the inhibition of VEGF-A, stimulated by the phosphorylation/activation of ERK, Akt, and p70S6K, and the downregulation of VEGFR-2 and MMP-2 in human umbilical vein endothelial cells [109].…”
Section: Other Propertiesmentioning
confidence: 99%
“…Another study on 11 healthy subjects indicated that using a leaf extract of paper mulberry for 12 weeks showed beneficial effects on hair growth, indicated by increased total hair count as compared with the start date of the trial. The underlying mechanism might be through regulating the WNT-β-catenin and STAT6 pathways to promote the proliferation of dermal papilla cells [98]. These data suggest the potential application of paper mulberry in hair-care products in cosmetics.…”
Section: Hair Protection and Hair Growthmentioning
confidence: 82%
“…TGF-β1 and its receptors are involved in the catagen phase of the hair cycle and promote tissue remodeling and apoptosis [67]. the level of β-catenin protein; inhibited IL4-induced STAT6 phosphorylation; increased hair count after using the hair tonic for 12 weeks [37] Red Ginseng Oil C57BL/6 mice SKH-1 hairless mice 50% 1% Induction of hair growth; upregulated expression of β-catenin, phospho-GSK3β, Lef-1, Gli-1, Smoothened, Cyclin D1, Cyclin E, IGF-1 and VEGF; protective effect against UVC-induced skin damage in SKH-1 hairless mice by inhibiting inflammation and apoptosis [38] Thuja orientalis C57BL/6 mice 5.05 mg/cm 2 /day Induction of hair growth including hair number and size of hair follicles; induction of β-catenin and Shh protein expression [39] 3,4,5-tri-Ocaffeoylquinic acid…”
Section: Growth Factorsmentioning
confidence: 99%
“…The BP root extract contains flavonoids, which results in inhibitory effects on nitric oxide, inducible nitric oxide synthase, TNF-α, and IL-6 [143]. Treatment with BP eliminated IL-4-induced STAT6 phosphorylation in hDPCs [37].…”
Section: Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation